PENINGKATAN KEMAMPUAN GURU BAHASA INDONESIA DALAM MENYUSUN RENCANA PROGRAM PEMBELAJARAN (RPP) SDN 015 PAGARAN TAPAH DARUSSALAM MELALUI METODE PEMBERIAN TUGAS - Mukhlis (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
Based on classroom observations, several critical issues were identified, including the limited ability of Indonesian language teachers to design lesson plans (RPP), the use of learning devices merely as supplementary documents rather than as instructional necessities, and the fact that many teachers were unable to present lesson plans when requested because they had not prepared them. This study aimed to improve the competence of Indonesian language teachers in designing lesson plans (RPP) at SDN 015 Pagaran Tapah Darussalam through the task assignment method. The research employed a school action research design, with 12 Indonesian language teachers as the research subjects. The findings, derived from systematic analysis and discussion, indicate that the task assignment method effectively enhanced teachers’ ability to develop learning tools. This improvement was reflected in increased teacher engagement and acceptance of the intervention. Quantitatively, the percentage of teachers’ competence in preparing lesson plans increased from 56% in Cycle I to 79%